Pemberdayaan Masyarakat melalui Pengelolaan Hutan Pinus di Kecamatan Linge Aceh Tengah - Siti Ikramatoun; Khairulyadi Khairulyadi; Riduan Riduan (Jurnal Sosiologi Agama Indonesia (JSAI), 2020)
This article aims to describe community empowerment through the management of the pine forest owned by PT Tusam Hutan Lestari in Linge District, Central Aceh. How the relationship between the community and PT Tusam Hutan Lestari as the owner of a pine forest management permit in Linge District. The approach used in this article is a qualitative method with a descriptive model. The informant was selected using a purposive technique and data sourced from observations, interviews, and literature studies. The results of this study indicate that community empowerment through pine forest management in Linge District had a positive impact on the community. Utilization of the company's production forest by the community has encouraged the emergence of community economic empowerment because the granting of land management permits and tapping of pine sap by the community is accompanied by mentoring by the company and provision of training and the formation of company partners. It also means that there is an economic exchange relationship between the company and the community, and this relationship is a mutually beneficial relationship between the community and the company.